2003
DOI: 10.1051/forest:2002075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cotyledon removal on early seedling growth in Quercus robur L.

Abstract: -The process of resource transfer from seed to growing plant, in terms of dry matter and nitrogen, was studied in Quercus robur L. seedlings. In a factorial experiment, seedlings were subjected to cotyledon excision and shading just after shoot emergence. In another experiment, we removed the cotyledons at emergence and 7, 14 and 21 days later. The transfer of resources from cotyledons to growing plant seemed to be almost complete at a very early stage. Cotyledon excision just after shoot emergence resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
(30 reference statements)
8
40
0
4
Order By: Relevance
“…In fact, one of these seedlings with a removed acorn managed to survive until the end of this experiment. Similar results have been found by others (García-Cebrian et al, 2003) who showed that seedling survival of Quercus robur was not affected by the removal of cotyledons, although it did have negative consequences for seedling growth (notably stem length and biomass). It appears that cotyledon removal only has dramatic effects when it happens in the first week after emergence.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, one of these seedlings with a removed acorn managed to survive until the end of this experiment. Similar results have been found by others (García-Cebrian et al, 2003) who showed that seedling survival of Quercus robur was not affected by the removal of cotyledons, although it did have negative consequences for seedling growth (notably stem length and biomass). It appears that cotyledon removal only has dramatic effects when it happens in the first week after emergence.…”
Section: Discussionsupporting
confidence: 78%
“…At the end of flooding (day 34), reduction in leaf expansion may have altered source-sink relationships leading to a significant decrease in leaf amino acid content. The transfer of resources from cotyledons to growing seedlings seems to be almost complete at a very early stage [18]. In our experiment, under flooding stress, the decrease in biomass and amino acid content of cotyledons was more pronounced in control seedlings than in stressed seedlings.…”
Section: Nitrate Reductionmentioning
confidence: 58%
“…These results indicated that resource transfer from cotyledon to growing organs was disturbed even six weeks ago after shoot emergence. In fact, according to García-Cebrián et al [18], the extent of transfer reaches 80% of the biomass and 73% of the nitrogen content of the cotyledon respectively only 14 days after shoot emergence.…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…The removal of cotyledons 3 weeks after emergence did not influence the mass and height of Quercus robur seedlings (Andersson and Frost 1996). However, significant consequences of cotyledon removal on seedling mass were observed when the cotyledons were removed during the first 2 weeks after emergence (Garcia-Cebrian et al 2003). Our results show that the degree of acorn damage is very important.…”
Section: Biological Aspectsmentioning
confidence: 63%
“…Oak germinates hypogeally; the acorns remain below the ground surface and do not take part in photosynthetic activity, remaining storage organs only. The consequences of cotyledon removal just after emergence of Quercus robur seedlings are very significant for seedling growth (Garcia-Cebrian et al 2003). The growth, maturation and flowering of some dicotyledonous grassland species is also affected by cotyledon damage (Hanley and Fegan 2007).…”
Section: Introductionmentioning
confidence: 99%